The effects of simple febrile seizure on apoptosis molecular alterations in hippocampus of rat neonates - Mohamad Javad Saeedi-Boroujeni; Ghasem Sazegar; Javad Hami (University of Social Welfare and Rehabilitation Sciences, 2013)
Objective: Febrile seizures are the most common seizure disorder in childhood, and occur in 2-5% of children. While simple febrile seizures are frequently described as inoffensive disorder there are evidence suggesting the association between simple febrile seizures and hippocampal abnormalities in adulthood. This study was designed to evaluate the protein levels of Bcl-2 and Bax in the rat neonates' hippocampus due to Simple Febrile Seizure. Materials & Methods: Febrile seizure was modeled by hyperthermia-induced seizure in 22-day-old male rats using a hot water bath. Animals were divided into two groups based on the presence or absence of seizure behaviours: Hyperthermia without seizure (n=10) and Hyperthermia with seizure (n=10). To control the effects of environmental stress a sham-control group was also added to the study (n=10). The rats' hippocampi were removed 15 days after hyperthermia. The expression of Bax and Bcl-2 proteins were measured using Western Blotting technique. Results: Our results showed that the protein levels of Bcl-2 were significantly lower in hippocampus of hyperthermia with seizure group rats than that of the sham-control and Hyperthermia without seizure groups. Whereas, the levels of Bax protein i hippocampi of hyperthermia with seizure group animals showed a markedly upregulation, when compared to sham-control and Hyperthermia without seizure groups. Conclusion: Simple febrile seizure is associated with changes in the level of Bcl2 ,andBax proteins, indicating an apoptosis improvement in hippocampi of juvenile rats, which were measurable for at least 15 days.